Intracytoplasmic inclusion bodies associated with vesicular ulcerative and necrotizing lesions of the digestive mucosa in fallow deer (Dama dama L.) - Diaz, Regina; Rehbinder, Claes; Feinstein, Ricardo; Nikkilä, Tapio (Rangifer, 1990)
Intracytoplasmic epithelial inclusion bodies in the digestive mucosa of fallow deer (Dama dama L.) were found to most probably be the result of an unspecific degenerative or post mortal change. There are reasons to believe that this is true also for the inclusion bodies found in reindeer, roe deer and moose.